Aligning Information Systems Program with the New ABET-CAC Criteria: The Case of the American University of Kuwait. - Rababaah, Aaron (2020)
ABET recently revised their published list of program specific criteria. Beginning from the 2019-2020 cycle, all computing programs, including information systems, must meet the new criteria to receive ABET accreditation. This paper describes the procedure followed by the Computer Science and Information Systems (CSIS) Department at the American University of Kuwait (AUK) in aligning the information systems (IS) program with the new ABET-CAC criteria. The paper illustrates all the steps taken by the department from the initial preparation, measurements, and assessments of students' outcomes to the continuous improvement and closing the loop processes. This paper aims at sharing the methods and experiences of the CSIS Department at AUK, which may be beneficial for other institutions seeking ABET accreditation of their information systems programs.